Chemical Analysis of Sexual Lubricant Residue: A Comparison of Medical Examination Swabs Analyzed Using Spectroscopic Techniques - Safiya J. Best; Santana Thomas; Nancy Flynn; Candice Bridge (Forensic Sciences, 2023)
Sexual assault kits are the standard method for collecting and preserving sexual assault evidence. During the sexual assault examination, swabs are commonly used to collect bodily fluids as sexual assault evidence from the vagina, anus, mouth, and skin. The type of fiber swab used during collection can greatly influence the recovery of the substrate. In cases where lubricant residue may be present, it would be useful to identify the swab type that would be the most efficient in the collection of lubricant residues. In this study, four types of swabs with different fibers (i.e., cotton, polyester, rayon, and foam) with sexual lubricants present, were extracted in various solvents. The extracts were analyzed using attenuated total reflectance Fourier-transform infrared (ATR-FTIR) and Raman spectroscopy. The Pearson correlation coefficient (PCCs) test was applied to determine a pairwise comparison between swab lube extracts and the standard lubricant reference. Visual comparisons of the lubricant reference, blank fiber swab, and the fiber lubricant extract were used to determine peak overlap, significance, and matrix interference.